DETERMINANTS OF NEONATAL MORTALITY BASED ON THE 2017 INDONESIAN DEMOGRAPHIC AND HEALTH SURVEY (IDHS) - Fidya Rumiati; Asri C. Adisasmita (The Indonesian Journal of Public Health, 2021)
ABSTRACTInfant mortality is still a major health problem in Indonesia as 63% of deaths occur in the neonatal period. The trend of the neonatal mortality rate in Indonesia has decreased from 15 (2017) to 13 deaths per 1,000 live births (2018), but this does not meet the Sustainable Development Goals (SDGs) target. Evidence-based health interventions are based on determinants that most influences neonatal mortality. The purpose of this study was to determine the most influential determinants of neonatal mortality in Indonesia. This research is an analytic observational study that uses the 2017 Indonesian Demographic and Health Survey (IDHS) data, with a cross-sectional design. This study’s population was the last baby of married women of childbearing age (15-49 years) and was recorded in the 2017 IDHS with a sample of 15,102 babies. The outcome variable in this study was neonatal mortality. The analysis was conducted in stages, namely univariate analysis, bivariate analysis using the chi-square statistical test (X2), and multivariate analysis using logistic regression. The results showed that 85.71% of deaths occurred in the early neonatal period. The most influential determinants of neonatal mortality were male sex (adj OR = 2.91: 95% CI 1.78-4.76), low birth weight (adj OR = 12.08: 95% CI 7.38-18.86) and parity status ≥ 4 (adj OR = 2.11: 95% CI 1.22-3.61). Public health interventions aimed at reducing neonatal mortality should be linked to newborn and maternal characteristics that significantly influence Indonesia's neonatal mortality. Therefore, health services must consider adequate postpartum neonatal care that is fully integrated with medical care. Moreover, further prevention of potential factors that cause low birth weight before conception should be implemented and further control of births would optimize the family planning program. Keywords: gender, low birth weight, parity status, determinant, neonatal mortality, Indonesia